2007
DOI: 10.1038/sj.ejcn.1602934
|View full text |Cite
|
Sign up to set email alerts
|

Weight catch-up and achieved schooling at 18 years of age in Brazilian males

Abstract: Objective: To assess the relationship between weight catch-up in infancy and achieved schooling at 18 years of age in Brazilian males. Subjects: All newborn infants in the city's hospitals were enrolled in 1982; 78.8% (2250) of all male participants were located at age 18 years when enrolling in the national army. Results: According to the Brazilian school calendar, 18-year-olds should be attending the 11th grade, but school failure was very common and 78.5% of all subjects had failed at least once. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
0
21
0
2
Order By: Relevance
“…Other than an analysis of attained schooling in Pelotas (17), we are not aware of other work addressing the topic. We found that weight gain from 0 to 24 mo had the strongest relationships with schooling outcomes followed by birthweight; weight gain from 24 to 48 mo had a weak or no relationship to schooling outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than an analysis of attained schooling in Pelotas (17), we are not aware of other work addressing the topic. We found that weight gain from 0 to 24 mo had the strongest relationships with schooling outcomes followed by birthweight; weight gain from 24 to 48 mo had a weak or no relationship to schooling outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have focused on cognitive development or achievement tests (1216) and few have dealt with schooling outcomes (17). Studies are particularly needed from low- and middle-income countries (LMIC), where the importance of establishing these relationships for policies and programs is greater due to high rates of growth failure and low schooling.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has also been suggested that rapid weight gain in the first years of life may reverse the long-term consequences of intrauterine growth restriction. For example, among Brazilian infants born small for gestational age (a proxy of intrauterine growth restriction), rapid weight gain in the first two years of life is related to higher achieved schooling in early adulthood [30] and higher birthweight in the next generation [31]. Therefore, promotion of weight gain in the first years of life may have positive long-term and intergenerational consequences [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2012 Save the Children Report, children whose physical and mental development are stunted by undernutrition will earn less on average as adults, and this represents a loss of human potential associated with a wage reduction of around 20%. 21 Furthermore, evidence suggests that promotion of growth among children under 2 years of age has long-term consequences on human capital, [22][23][24] whereas it does not increase the risk of cardiovascular disease. 25 This study was conducted in a population that survives in great environmental and socioeconomic precariousness, but that is in the process of nutritional transition.…”
mentioning
confidence: 99%
“…These findings are important because evidence suggests that larger HC should lead to better long-term outcomes. 9,17,[21][22][23][24][25] These aspects can and should be used as additional argument to persuade mothers to breastfeed their children for > 4 months.…”
mentioning
confidence: 99%